Interventions to improve spiritual well-being in adult patients with cancer: a rapid review - Maria Komariah; Iwan Shalahuddin; Ade Haniah Sya’adah Rahmaniah; Cindy Puspita Sari; Hera Prafitri Rusmana; Nadilla Cynthia Nur Fikriyah; Shofura Kamil Pasya (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The diagnosis of cancer causes significant suffering and anxiety to the patient and threatens the meaning of the patient's life leading to the appearance of a sense of disintegration, so the fulfillment of the spiritual needs of the cancer patient is necessary. Addressing the spiritual needs of cancer patients plays a role in accelerating recovery and achieving spiritual well-being. The purpose of this study was to find out recommendations for interventions in improving the spiritual well-being of adult patients with cancer. This research is a rapid review study with article searches using EBSCOhost, PubMed, and Google Scholar databases. The criteria for listing articles taken include research articles from the last 10 years during 2012-2022, randomized controlled trials or quasi-experiments, English, and full text. As a result of searching the literature, 8 articles from all three databases met the criteria. Based on these results, it was found that there are several interventions that can be done, including spiritual therapy, spiritual group therapy, mindfulness, spiritual counseling and Islamic-based caring. Of the several interventions obtained, it is recommended that Islam based caring because it is suitable to be applied in Indonesia, also features the practice of do'a and dhikr meditation that can be practiced daily and is proven to improve the spiritual well-being of adult patients with cancer. More research on online mindfulness therapy in cancer patients performing treatments at home and in hospitals